2008
DOI: 10.1016/j.jcsr.2008.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Residual stresses in cold-rolled stainless steel hollow sections

Abstract: a b s t r a c tStainless steel exhibits a pronounced response to cold-work and heat input. As a result, the behaviour of structural stainless steel sections, as influenced by strength, ductility and residual stress presence, is sensitive to the precise means by which the sections are produced. This paper explores the presence and influence of residual stresses in cold-rolled stainless steel box sections using experimental and numerical techniques. In previous studies, residual stress magnitudes have been infer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(99 citation statements)
references
References 14 publications
0
98
0
1
Order By: Relevance
“…While the patterns and magnitudes of residual stresses in structural carbon steel cross-sections have been studied extensively [12,13], those in stainless steel sections [5,14,15], particularly welded sections [16][17][18][19] have received less attention.…”
Section: Residual Stress Measurementsmentioning
confidence: 99%
“…While the patterns and magnitudes of residual stresses in structural carbon steel cross-sections have been studied extensively [12,13], those in stainless steel sections [5,14,15], particularly welded sections [16][17][18][19] have received less attention.…”
Section: Residual Stress Measurementsmentioning
confidence: 99%
“…For cold-rolled and seam-welded stainless steel tubular sections, Young and Lui [40], Cruise and Gardner [41], Jandera et al [42] and Huang and Young [43] carried out careful residual stress measurements and concluded that the magnitude of the membrane residual stresses was small compared to that of the bending residual stresses. In addition, as highlighted in [40][41][42]44], the effect of the through-thickness bending residual stresses is inherently incorporated into the measured material properties, since the coupons straighten during tensile testing. Thus, explicit inclusion of residual stresses in the numerical models was deemed unnecessary.…”
Section: Basic Modelling Assumptionsmentioning
confidence: 99%
“…(6), for input into ABAQUS, where σ true is the true tress, pl ln  is the logarithmic plastic strain, and σ nom and ε nom are the engineering stress and strain, respectively. Residual stresses were not explicitly incorporated into the modelled sections, principally due to the negligible influence of membrane residual stresses on coldformed stainless steel tubular profiles and the inherent presence of the more dominant through-thickness residual stresses into the measured material properties [43][44][45]. With regards to end section boundary conditions, all degrees of freedom for the nodes of the loaded end were coupled to an eccentric reference point, which only allowed longitudinal translation and rotation about the axis of buckling, in order to simulate pin-ended boundary conditions.…”
Section: Basic Modelling Assumptionsmentioning
confidence: 99%